THE EFFECT OF DISCOUNT AND POSITIVE AFFECT ON FINANCIAL PLANNING THROUGH IMPULSIVE BUYING - Rinwantin Rinwantin; Yanti Pujiastuti (Faculty of Economic and Business, University of Pasundan, 2022)
Financial planning arrangements, can be seen from financial preparedness for emergencies, the community must be able to survive and anticipate unexpected needs. The Harbolnas phenomenon with the existence of free shipping and cashback in the marketplace can increase impulsive buying behavior and can affect emergency fund preparedness. This study aims to determine the effect of discounts and positive affect on financial planning mediated by impulsive buying variables. Respondents in this study amounted to 100 respondents. The results of the research processed using SPSS contain the conclusion that the positive affect variable has a Sig value of less than 0.05 (0.002 < 0.05), which means that the hypothesis is accepted. The positive affect variable has a Sig value of less than 0.05 (0.000 < 0.05). which means the hypothesis is accepted.